Análisis del impacto socioambiental de las hidroeléctricas El Quimbo e Hidroituango en Colombia (2022)
This degree work analyzes the socio-environmental impacts of the El Quimbo and Hidroituango hydroelectric plants in Colombia, through a bibliographic review. The search for information covers the historical period between 2000 and 2020, in order to obtain updated and useful information for the study. The SCOPUS database is used, obtaining a total of 1127 documents that include articles, books, papers and reviews. After the literature review, the most relevant information resources for the construction of this document were selected. The general objective and the specific objectives are set out in the first chapter. The second chapter includes the reference framework in which the terms and definitions necessary for understanding the main theme of the project, hydraulic energy, hydroelectric plants and their classification and the global panorama of this energy are presented.